Role of Hematopoietic Stem Cell Transplantation in Relapsed/Refractory Hodgkin Lymphoma - Carella, Angelo Michele (Università Cattolica del Sacro Cuore, 2012)
Hodgkin lymphoma is one of the most curable human tumors. Despite this, about 30% of these patients relapsed or are primary refractory to the first line treatment. Autografting is generally considered the standard of care for these patients. Alternative salvage strategies have been evaluated such as high dose sequential and tandem autografting strategies. In younger patients, refractory or early relapsed after autografting, allogeneic stem cell transplantation has been employed but this approach has been followed by significant concerns since the treatment related mortality, often exceeded 40–50%, and relapses were not uncommon. It is clear that patient selection remains an issue in all allografting reports. At the end, new drugs and novel treatment strategies, that are based on our understanding of the disease biology and signaling pathways, are needed to improve treatment outcome for these patients. The two leading compounds Brentuximab Vedotin and Panobinostat, are currently under evaluation in several clinical trials.